Process Analysis and Comparison of Biogas Techniques - Rabia A. Almabrouk; Nasreddin O. Tarhabat; Omar A. Algeidi (Journal of Scientific and Human Dimensions, 2026)
Upgrading biogas to high energy biomethane is commonly utilized to produce substitute natural gas (SNG) where the most crucial operation is a separation of CO2from biogas, which is carried out by several technologies such as, amine scrubbing, cryogenic separation. The aim of this study, was to perform a design and optimization comparative process for upgrading section of biogas production and processing plant of the two technologies (absorption and cryogenic separation).The two technologies were examined and analyzed to assess their pros and cons in order to choose the most appropriate method to be implemented, where three aspects were chosen for the assessment: (1) process technology and product quality, (2) methane recovery and losses, (3) energy consumption and economy. The research was carried out using a package of commercial software's including, Aspen HYSYS v11, Exchanger design and rating (EDR), Aspen Process Economic Analyzer (APEA) and MS excel.The obtained results of amine process show that the total energy and power consumption in the optimized case are reduced by 73% and 11% respectively in comparison with the base case, furthermore the methane losses in the entire system were reduced by 27% and consequently the methane recovery was increased to 99,93%. Due to the implementation of heat integration process by cryogenic process, the total energy consumption in the optimized case was reduced by 44% in comparison with the base case, in the other hand, implementation of the methane recovery stage reduces the methane losses in the entire system by 76% and consequently the methane recovery in the upgraded biogas stream is increased from 85.15% to 95.91%, however, it causes slight increasing in the total power from 230.7 kW to 241.7 kW, moreover, the CO2 mole fraction in the upgraded biogas remains within the limits (
Keywords: The Process of Converting Biogas; Biomethane; To Produce Natural Gas; Separating Carbon Dioxide; Integrating Heat